Gene mapping reveals the association between tyrosine protein kinase Abl1 and the silk yield of Bombyxmori. (8th March 2021) - Luan, Y.; Li, C.; Zuo, W.; Hu, H.; Gao, R.; Zhang, B.; Tong, X.; Lu, C.; Dai, F.
Summary: The Z chromosome of the silkworm contains a major gene that influences silk yield. This major locus on chromosome Z accounts for 35.10% of the phenotypic variance. The location and identification of the gene have been a focus of silkworm genetics research. Unfortunately, identification of this gene has been difficult. We used extreme phenotype subpopulations and selected from a backcross population, BC1 M, which was obtained using the high‐yield strain 872B and the low‐yield strain IS‐Dazao as parents, for mapping the gene on the chromosome Z. The candidate region was narrowed down to 134 kb at the tip of the chromosome. BmAbl1 in this region correlated with silk gland development by spatiotemporal expression analysis. This gene was differentially expressed in the posterior silk glands of the high‐ and low‐yield strains. In BmAbl1, an insertion–deletion (indel) within the 10th exonic region and an SNP within the 6th intronic region were detected and shown to be associated with cocoon shell weight in 84 Bombyx mori strains with different yields. Nucleotide diversity analysis of BmAbl1 and its 50 kb flanking regions indicated that BmAbl1 has experienced strong artificial selection during silkworm domestication. This study is the first to identify the genes controlling silk yield in the major QTL of the Z chromosome using forward genetics.